Three new species of Neolethaeus Distant (Hemiptera: Lygaeoidea: Rhyparochromidae: Lethaeini) from China, with a key to the Chinese species - Li, Junlan; Bu, Wenjun (Zootaxa, 2006)
Three new species, Neolethaeus densus sp. n., Neolethaeus maculacellus sp. n., and Neolethaeus distinctus sp. n. are described from China. Photographs of the new species and illustrations of genital structures are given. A key to all Chinese species is included.